An analysis of the changes in the seasonal patterns of tourist behavior during a process of economic recovery - Guaita Martínez, José Manuel; Martín Martín, José María; Ostos‐Rey, María S. (Technological Forecasting and Social Change, 2021)
This paper studies how the improvement of the economic situation influences the behavior patterns of national and foreign tourists in relation to the seasonal trends that define their trips. After analyzing the patterns developed by tourists arriving to Spanish destinations, it has been found that in the period 2013–2018, the seasonality levels of destinations associated with secondary trips has decreased, while the number of said trips and their length has increased. At the same time, the number of trips made to coastal destinations, associated with the main holiday trip, does not grow as much. Additionally, these trips are shorter and an increase in the seasonality level can be seen in some cases.
Keywords: tourist behavior; seasonality; Spain; economic growth; JCR; Scopus